PENINGKATAN KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR MENGGUNAKAN MODEL PJBL BERBANTUAN MEDIA LAPIN UNTUK SISWA KELAS VI SD - Imaculata Wahyuni, Maria; Herlina Dwi Hadiyanti, Agnes (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study was motivated by the low ability of creative thinking and learning outcomes of students in grade VI of SD Kanisius Demangan Baru1.The objectives of this study are: (1) To describe efforts to improve creative thinking skills and learning outcomes using the PJBL model assisted by LAPIN media in class VI of Kanisisus Demangan Baru 1 Elementary School; (2) To improve creative thinking skills using the PJBL model assisted by LAPIN media in class VI of Kanisius Demangan Baru 1 Elementary School; (3) To improve learning outcomes using the PJBL model assisted by LAPIN media in class VI of Kanisius Demangan Baru 1 Elementary School.This type of research is Classroom Action Research (PTK). The subjects of this study were VI grade students of SD Kanisius Demangan Baru 1 in the 2023/2024 academic year. The object of this research is the improvement of creative thinking skills and learning outcomes using the PJBL model assisted by LAPIN media. Data collection techniques were obtained by observation, questionnaires, and tests. The data analysis technique used in this research is quantitative and qualitative analysis.The results showed that the PJBL model assisted by LAPIN media could improve creative thinking skills and learning outcomes, the average value of creative thinking skills from the initial condition of 55.11 with criteria (Less Creative), in cycle 1 increased to 67.70 with criteria (Quite creative), in cycle II increased to 80.01 with criteria (Creative). The average value of student learning outcomes from the initial condition value of 61.00, increased to 76.81 in cycle 1, and in cycle II increased to 86.81.